2020
DOI: 10.1111/ppc.12452
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between depression and loneliness levels of the students at the faculty of health sciences and the factors affecting them

Abstract: Purpose: The aim of this study is to determine the relationship between the loneliness and depression levels of students studying at Inonu University, Faculty of Health Sciences, Departments of Nursing, Midwifery, Physiotherapy, Audiology and Child Development and the factors that affect these levels. Design and Methods:This descriptive cross-sectional study which used a sociodemographic information form, the UCLA Loneliness Scale and the Beck Depression Inventory included 1004 students.Findings: According to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 27 publications
1
17
2
Order By: Relevance
“…Previous research focused on SA and its impact on face‐to‐face communication revealed that loneliness and SA are positively correlated and that loneliness is the strongest determinant of SA 3,18‐22 . It is known that the loneliness is a serious problem in young adolescents and the problematic mobile phone use is an individual coping method for loneliness in this population 15,23 . NSs use smartphones more intensively to address both the problems they face in adapting to a new city and university environment, as well as the loneliness of leaving the social environment 23 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous research focused on SA and its impact on face‐to‐face communication revealed that loneliness and SA are positively correlated and that loneliness is the strongest determinant of SA 3,18‐22 . It is known that the loneliness is a serious problem in young adolescents and the problematic mobile phone use is an individual coping method for loneliness in this population 15,23 . NSs use smartphones more intensively to address both the problems they face in adapting to a new city and university environment, as well as the loneliness of leaving the social environment 23 .…”
Section: Introductionmentioning
confidence: 99%
“…3,[18][19][20][21][22] It is known that the loneliness is a serious problem in young adolescents and the problematic mobile phone use is an individual coping method for loneliness in this population. 15,23 NSs use smartphones more intensively to address both the problems they face in adapting to a new city and university environment, as well as the loneliness of leaving the social environment. 23 This makes NSs feel lonelier.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the increasing feeling of loneliness, mental health problems are quite common among university student populations (Musiat et al, 2018). Various studies in the literature have shown that loneliness is a serious issue determined to be highly associated with pathological conditions such as depression (Kılınç et al, 2020;Lee & Bierman, 2019;Yavuzer et al, 2019), anxiety (Moeller & Seehuus, 2019), and suicide (Chang et al, 2019;Chang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%